Prevalence of osteoporosis and factors associated with osteoporosis in women above 40 years in the Northern Part of Saudi Arabia - Oommen, Anitha; AlZahrani, Ibrahim (International Journal of Research in Medical Sciences, 2017)
Background: Women have lower bone density than men and they lose bone mass more quickly as they advance in age, which leads to osteoporosis. The Saudi Diabetes and Endocrine Association in the Eastern Province revealed that 30 to 50% of Saudi women above 40 years of age develop osteoporosis. Factors related to the development of osteoporosis include poor diet, low calcium intake, vitamin D deficiency, sedentary lifestyle and smoking. Previous studies have shown that there is a high prevalence of vitamin D deficiency in Saudi women. Methods: The present study was done in 100 Saudi women above 40 years of age who were outpatients in Arar Central Hospital during a period of four months. After taking an informed consent, data was collected relating to the risk factors, vitamin D levels were assessed and the patients underwent a Dual Energy X-ray Absorptiometry (DEXA) scan. Results: The results showed that 82% of Saudi women patients had vitamin D deficiency. Only 21% of women were exposed to sunlight. 58% of the women had low BMD (18% with osteoporosis and 40% with osteopenia). Only 5% of patients took Vitamin D and Calcium rich diet and 7% were in the habit of doing exercise. There was a significant association between bone mass density and exercise when Fisher’s exact test was used (P value < 0.05) Conclusion: Prevalence of osteopenia is higher than osteoporosis in the Saudi women above 40 years in the Northern part of Saudi Arabia. The major cause of low BMD is lack of exercise even though there is a high prevalence of Vitamin D deficiency.